Exploring the barriers and driving factors in implementing building Information Modelling (BIM) in the malaysian construction industry - a preliminary study - Zuhairi, Abd. Hamid (The Institution of Engineers, Malaysia (IEM), 2014)
Link to publisher’s homepages at http://www.myiem.org.my/